Phosphodiesterase-5 Inhibitors: Future Perspectives - Konstantinos, Giannitsas; Petros, Perimenis (Current Pharmaceutical Design, 2009)
PDE-5 inhibitors were originally studied in cardiovascular indications but were later developed and approved for on-demand treatment of erectile dysfunction (ED). A few years ago sildenafil was approved for the treatment of pulmonary hypertension, thus renewing interest in cardiovascular applications, and tadalafil became available in oncedaily formulations for erectile dysfunction management. Given the wide distribution of phosphodiesterase-5 throughout the body and its involvement in multiple functions, what can one expect in the future? To answer this we reviewed studies involving PDE-5 inhibitors that were published within the past three years and searched the US National Institutes of Health clinical trial registry for ongoing ones. PDE-5 inhibitors are being actively investigated in many disease states, with interest focusing mainly on urology and cardiovascular medicine. In urology erectile dysfunction is the primary target, followed by BPH-related lower urinary tract symptoms. As far as cardiovascular medicine is concerned, treatment of heart failure is the indication where PDE-5 inhibitors seem to be closer to clinical application but preclinical data also support a role in cardiac preconditioning.
Keywords: indications